2016
DOI: 10.1039/c6ra21253k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of fluorinated donepezil by palladium-catalyzed decarboxylative allylation of α-fluoro-β-keto ester with tri-substituted heterocyclic alkene and the self-disproportionation of its enantiomers

Abstract: Catalytic asymmetric synthesis of fluorinated donepezil, a promising new therapeutic agent for Alzheimer's disease, was achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…One new, highly promising candidate for the treatment of Alzheimer's disease and other Alzheimer-like diseases is the fluorinated analog of donepezil, 89 44 ( Fig. 15 ), specifically designed to combat the problem of in vivo racemization of donepezil, though there is only a minor difference between the bioactivities of the two enantiomers of donepezil.…”
Section: Implications Of Broader Significancementioning
confidence: 99%
See 1 more Smart Citation
“…One new, highly promising candidate for the treatment of Alzheimer's disease and other Alzheimer-like diseases is the fluorinated analog of donepezil, 89 44 ( Fig. 15 ), specifically designed to combat the problem of in vivo racemization of donepezil, though there is only a minor difference between the bioactivities of the two enantiomers of donepezil.…”
Section: Implications Of Broader Significancementioning
confidence: 99%
“…However, not only is 44 much more potent than donepezil against acetylcholinesterase (1.3 nM vs. 5.9 nM), it could be that there are large bioactivity differences between the two enantiomers of 44 based on the 60-fold difference between the two enantiomers of a very similar difluoro analog of donepezil towards rat brain acetylcholinesterase. Thus, Shibata et al , upon noticing a rather minor but unexpected change in the ee when conducting a non-asymmetric transformation of a scalemic sample of 44 , specifically tested 89 for the SDE when performing gravity-driven column chromatography on a sample of 44 ( Fig. 15 ) with 44% ee and observed a substantially high Δee of 43%.…”
Section: Implications Of Broader Significancementioning
confidence: 99%
“…Over the last decade, systematic research into the phenomenon of the self-disproportionation of enantiomers (SDE) [ 5 , 6 , 7 , 8 , 9 , 10 ] has clearly revealed that the accuracy in reporting the stereochemical outcome of enantioselective reactions represents a major issue of concern in terms of data integrity and the understanding of the stereochemical mechanisms at play and the interpretation of the results. It has been unequivocally shown that any physicochemical treatment, including achiral chromatography [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ] or even rotary evaporation [ 40 , 44 ], of a scalemic sample inevitably leads to fractionation of the material into portions of variable enantiomeric excess (ee), with consequent erroneous reporting of the stereochemical outcome if due care is not taken. Yet, there is a deficiency in the general understanding and appreciation of the SDE phenomenon, even though it has been known for a considerable length of time now.…”
Section: Introductionmentioning
confidence: 99%
“…Our primary goal has been to develop fluorinating and fluoro-functionalized reagents for fluorination [ 18 19 ], trifluoromethylation [ 13 , 18 19 ], trifluoromethylthiolation [ 12 , 21 ] and pentafluoroarylation [ 22 23 ]. Utilizing these reagents, we have successfully synthesized a wide variety of bioactive organofluorine compounds [ 24 30 ] including fluorinated thalidomide (antitumor) [ 24 ], fluorinated donepezil (cholinesterase inhibitor) [ 25 ], and fluorinated camptothecin (anticancer) [ 26 ]. During our research programs focused on the development of novel reagents for fluoro-functionalization [ 12 13 16 23 ], as well as the design and synthesis of biologically active fluorine-containing compounds [ 24 28 ], we noted that a series of fluoro-functionalization reagents could themselves be highly potential drug candidates.…”
Section: Introductionmentioning
confidence: 99%